MENELUSURI TRADISI MAUDU LOMPOA DI DESA CIKOANG - Wulandari, Andi Ulfa (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2024)
This article examines the Maudu Lompoa tradition in Cikoang Village, Takalar Regency, as a form of religious expression rootedin symbolic meanings and spiritual values. Based on a qualitative descriptive approach, this study incorporates anthropological, sociological, and philosophical methods. The findings reveal that Maudu Lompoa is a local form of the Prophet Muhammad’s mawlid, framed through cultural symbols such as julung-julung, decorated eggs, and zikir stages. This ritual strengthens spiritual ties to the Prophet Muhammad and serves as a mechanism for reinforcing the Sayyid community’s identity. The study affirms that Cikoang’s local Islam is a unique blend of theological doctrine and cultural expression.